2020
DOI: 10.1088/1758-5090/ab5f50
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel co-networks of gelatine methacrylate and poly(ethylene glycol) diacrylate sustain 3D functional in vitro models of intestinal mucosa

Abstract: Mounting evidence supports the importance of the intestinal epithelial barrier and its permeability both in physiological and pathological conditions. Conventional in vitro models to evaluate intestinal permeability rely on the formation of tightly packed epithelial monolayers grown on hard substrates. These two-dimensional models lack the cellular and mechanical components of the non-epithelial compartment of the intestinal barrier, the stroma, which are key contributors to the barrier permeability in vivo. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 56 publications
(81 reference statements)
4
33
1
Order By: Relevance
“…GelMA-PEGDA hydrogels bioprinted with the low cost DLP-SLP instrument sustain cell culture effectively NIH-3T3 mouse embryonic fibroblasts were chosen to validate the suitability of our setup for bioprinting, since they are commonly used for cell encapsulation experiments (13,56). In addition, these cells represent the fibroblast cell population within the stromal compartment of our intestinal model.…”
Section: Swelling Mechanical and Diffusion Properties Of Bioprinted G...mentioning
confidence: 99%
See 2 more Smart Citations
“…GelMA-PEGDA hydrogels bioprinted with the low cost DLP-SLP instrument sustain cell culture effectively NIH-3T3 mouse embryonic fibroblasts were chosen to validate the suitability of our setup for bioprinting, since they are commonly used for cell encapsulation experiments (13,56). In addition, these cells represent the fibroblast cell population within the stromal compartment of our intestinal model.…”
Section: Swelling Mechanical and Diffusion Properties Of Bioprinted G...mentioning
confidence: 99%
“…While in recent years there has been a lot of efforts to produce engineered tissues that recapitulate the architecture of the intestinal tissue, in most of the cases those have been limited to represent only the epithelium. Mostly, this is due to the use of complex fabrication methods based on replica moulding that are not friendly with embedding cells within the matrix (11, 12) or the use of relatively high dense matrices that do not allow cell survival (13, 14). Recently, some attempts have been made to include fibroblasts to mimic the stromal tissue in flat constructs (15), demonstrating the relevance of testing drug absorption in the presence of a full mucosa tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the incorporation and amplification of various cells in GelMA hydrogels have been used extensively due to their combined properties of mechanical characteristics, the presence of bioactive peptide sequences, and biocompatibility [31]. It has been shown that a combination of poly ethylene glycol diacrylate and GelMA (PEGDA/GelMA) creates a hydrogel with stronger mechanical properties and appropriate degradation rates compared with pure GelMA hydrogel [32]. Moreover, the incorporation and proliferation of various cell types in GelMA hydrogels have been extensively used.…”
Section: Natural Hydrogelsmentioning
confidence: 99%
“…Nanoconfined material structures, including polymers as well, due to the wide range of unique structural features, properties, and effects arising under nanocompartmentalized conditions, have created significant worldwide interest over the last couple of years (see e.g., references [ 1 , 2 , 3 , 4 , 5 , 6 ] and references therein). The recently emerged polymer conetworks, especially amphiphilic conetworks (APCNs), composed of covalently or supramolecularly bonded, otherwise immiscible, hydrophilic and hydrophobic polymer chains, belong to such nanophase-separated materials with mutually nanoconfined macromolecular components [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Considering that polymers containing imidazole rings, which also play a pivotal role in the major biopolymers and compounds of living organisms, such as DNA, RNA, proteins, enzymes, hormones, vitamins, etc., provide various advantageous properties, like water solubility, strong metal ion coordinating ability, protonation, and alkylation possibilities, we have recently explored the synthesis, nanophasic structure, and properties of poly(1-vinylimidazole)- l -poly(tetrahydrofuran) (PVIm- l -PTHF) and poly(1-vinylimidazole)- l -poly(propylene...…”
Section: Introductionmentioning
confidence: 99%